1993
DOI: 10.1016/0014-5793(93)80449-5
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of the type III iodothyronine deiodinase with the affinity label N‐bromoacetyl‐triiodothyronine

Abstract: The type III iodothyronine deiodinase (ID-III) catalyzes the inner ring deiodination and, thus, the inactivation of the thyroid hormones T4 and Tj. ID-III activity in rat brain, rat placenta and embryonic chicken liver is inhibited by the affinity label N-bromoacetyl-T, (BrAcT,) with an affinity similar to that of T,. Reaction of rat brain and placenta microsomes with BrAc['*'I]T, resulted in the extensive labeling of a 32 kDa protein (~32). However, p32 was also prominently labeled in fetal rat liver microsom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Affinity labeling with BrAc[ 125 I]T 3 was also used for the quantitation of D1 enzyme expression levels by saturation analysis, allowing estimation of the D1 substrate turnover number in microsomal preparations and homogenates of transfected cells (41,50). With regard to affinity labeling of D3 with BrAcT3 results have been confusing (51)(52)67). Initial experiments with brain and placenta microsomes revealed a good correlation between affinity labeling of a 32-kDa protein (p32) and inactivation of D3 by unlabeled BrAcT3 (51,52).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Affinity labeling with BrAc[ 125 I]T 3 was also used for the quantitation of D1 enzyme expression levels by saturation analysis, allowing estimation of the D1 substrate turnover number in microsomal preparations and homogenates of transfected cells (41,50). With regard to affinity labeling of D3 with BrAcT3 results have been confusing (51)(52)67). Initial experiments with brain and placenta microsomes revealed a good correlation between affinity labeling of a 32-kDa protein (p32) and inactivation of D3 by unlabeled BrAcT3 (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to affinity labeling of D3 with BrAcT3 results have been confusing (51)(52)67). Initial experiments with brain and placenta microsomes revealed a good correlation between affinity labeling of a 32-kDa protein (p32) and inactivation of D3 by unlabeled BrAcT3 (51,52). However, when p32 was also detected in tissues with low or unde-tectable D3 activity and p32 labeling was not prevented by substrates of D3, it was concluded that p32 does not represent D3 protein (51,52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…D3 is found in many tissues, predominantly in the brain and in the placenta, and levels usually remain stable over a wide range of metabolic states Chanoine et al, 1993;Schoenmakers et al, 1993Schoenmakers et al, , 1995. As shown in Table 2, there was no effect of MeI on brain D3 activity in the exposed rats.…”
Section: D3 Analysismentioning
confidence: 84%
“…Results (mean ± SD) are presented as percent of control, which is the D2 activity in the brain homogenates from rabbits not exposed to MeI. quantities of D3 that likely protect the fetal compartment from toxic levels of maternal iodothyronines Chanoine et al, 1993;Schoenmakers et al, 1993Schoenmakers et al, , 1995. Indeed, the rabbit placenta contains ~10-fold higher D3 levels than were observed in the rat brain (195.2 ± 63.1 fmol T2 produced/mg protein/h).…”
Section: D3 Analysismentioning
confidence: 94%